Adaptação transcultural e validação semântica do instrumento Necpal Ccoms-Ico© para a língua portuguesa - Santana, Marcella Tardeli Esteves Angioleti [UNIFESP] (2018)
Objectives: To describe the translation and cross-cultural adaptation process of NECPAL CCOMS-ICO© tool to Portuguese language and to analyze semantic validity, as well as the content of the tool. Methods: This work consists of a methodological research about NECPAL CCOMS-ICO© tool cross-cultural adaptation from its original version in Spanish to Portuguese and measurement of semantic and content validities after translation process. The cross-cultural adaptation process was conducted according to Beaton recommendations, following the next steps: translation; translation synthesis; back-translation; analysis of semantic, idiomatic, conceptual and cultural equivalences of translated and back-translated tool versions by an expert committee composed of nine members, resulting in a pre-final version, which has been submitted to the authors of original tool to approval. Field testing was then performed, involving 35 health professionals. IVC was calculated to analyze semantic and content validities. Results: Cross-cultural adaptation process allowed us to construct of the final version of this tool, which is now named NECPAL-BR. The analysis of Content Validity, performed during expert committee evaluation, showed IVC 0.87. Collected data from pre-testing step enabled the analysis of Semantic Validity. The IVC observed at this step was 0.94. Conclusions: Considering IVC results, we have concluded that the tool has understandable and relevant items. In other words, there is agreement between requested capability in a specific domain and requested performance in the test conceived to measure this domain, confirming Semantic and Content Validities of the tool in its adapted version to Brazilian Portuguese.